Revision of the Global Fauna of Leptochela Stimpson, 1860 (Crustacea: Decapoda), Highlighting Phylogenetic Clades and a New Species - Alexander L. Vereshchaka; Anastasiia A. Lunina; Dmitry N. Kulagin; Jørgen Olesen; Laure Corbari (Diversity)
Leptochela Stimpson (1860) is a shallow-water, benthopelagic genus within the predominantly pelagic superfamily Pasiphaeoidea. We inventoried a global fauna of 17 currently valid species of Leptochela and identified a newly discovered eighteenth species. Our analysis combined both morphological and molecular data, using 13 characters (including two multistate characters) and 5 gene markers, respectively. The results revealed incongruence between the molecular and morphological datasets. However, our phylogenetic conclusions were based on a consensus approach, integrating morphological, molecular, and total evidence trees, which revealed three robust clades. We discuss the evolutionary development of quantitative and qualitative morphological traits in Leptochela and explore the potential causes of the incongruence between morphological and molecular signals, particularly in the context of pelagic eucarids transitioning from pelagic to benthopelagic habitats. Additionally, we describe the new species from Madagascar and provide a key to all known species of Leptochela.